Detection of Numerous Y Chromosome Biallelic Polymorphisms by Denaturing High-Performance Liquid Chromatography - Underhill, Peter A.; Jin, Li; Lin, Alice A.; Mehdi, S. Qasim; Jenkins, Trefor; Vollrath, Douglas; Davis, Ronald W.; Cavalli-Sforza, L. Luca; Oefner, Peter J. (Genome Research, 1997)
Y chromosome haplotypes are particularly useful in deciphering human evolutionary history because they accentuate the effects of drift, migration, and range expansion. Significant acceleration of Y biallelic marker discovery and subsequent typing involving heteroduplex detection has been achieved by implementing an innovative and cost-efficient method called denaturing high-performance liquid chromatography (DHPLC). The power of the method resides in its sensitivity and ability to rapidly compare amplified sequences in an automated manner. We have determined the allelic states of 22 Y polymorphisms; 19 of which are unreported, in 718 diverse extant chromosomes; established haplotype frequencies; and deduced a phylogeny. All major geographic regions, including Eurasia, are characterized by mutations reflecting episodes of genetic drift and expansion. Most biallelic markers are localized regionally. However, some show wider dispersal and designate older, core haplotypes. One transversion defines a major haplogroup that distinguishes a previously unknown deep, apparently non-African branch. It provides evidence of an ancient bottleneck event. It is now possible to anticipate the inevitable detailed reconstruction of human Y chromosome genealogy based on several tens to even hundreds of these important polymorphisms.
10.1101/gr.7.10.996